FEATURES OF DISTRIBUTION OF THE PARAMAGNETIC CENTERS ON THE AREA OF THE EMBA REGION OIL DEPOSITS - I.E. Kulbalina,; B.K. Kuspanova,; А.А.Kopasheva,; L.K. Madieva,; R.N. Nasirov, (Academic Scientific Journal of Chemistry, 2019)
In the oils of the studied deposits, we detected EPR signals both from vanadium ions and free radicals (FR). To determine their concentration, the most intense hyperfine structure (HFS) line was used among the complexes of tetravalent vanadium and a single line from the FR. There are no noticeable changes in the density of oil and the content of vanadium (IV) in the studied wells from the area of the Jurassic deposits of the Kyrykmyltyk field. It means that on the area, vanadium content in oil does not change, there is a good hydrodynamic communication between production wells, and the Kyrykmyltyk field belongs to low-vanadium oils. Uniform distribution of vanadium, is also established on the area of the Aptian, Albian and Cenomanian horizons of the Kara-Arna deposit and it characterizes the conditioned content of vanadium. Between the producing wells of each horizon there is observed a good hydrodynamic connection.